1984
DOI: 10.1111/j.1464-410x.1984.tb07168.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Sclerotherapy of Varicoceles—an Alternative to Conventional Surgical Methods

Abstract: Between May 1981 and October 1982, 259 varicoceles were identified by phlebography. It was possible to occlude 217 with Varicocid using a percutaneous Seldinger catheterisation technique under local anaesthesia. This method is an alternative to standard surgical techniques and has several advantages. It is cheap, it can be carried out on an out-patient basis, it lacks the risks associated with general anaesthesia and there are few complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
8

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 17 publications
(8 reference statements)
1
26
0
8
Order By: Relevance
“…These findings were supported by many radiographic studies, where they observed and identified these ana tomical arrangements, but these were only sporadic ob servations [11][12][13].…”
Section: Intraoperative Antegrade and Retrograde Spermatic Venographysupporting
confidence: 63%
See 1 more Smart Citation
“…These findings were supported by many radiographic studies, where they observed and identified these ana tomical arrangements, but these were only sporadic ob servations [11][12][13].…”
Section: Intraoperative Antegrade and Retrograde Spermatic Venographysupporting
confidence: 63%
“…The division of the testicular vein into medial and lateral branches was observed in many radiographic reports [9,[11][12][13] and was reported by us in a previous study [10]. According to this finding, we believe that the ideal site for testicular vein interruption should be below the site of the bifurcation.…”
Section: Discussionmentioning
confidence: 65%
“…16 But several reports supported the disadvantage of embolization due to the exposure to radiation and significant recurrence rates, in addition to the potential risk of vessel perforation and embolus migration. 21,22 At our department three methods of surgical ligation for left varicocele were performed, and the current data clearly demonstrated the minimal invasiveness of subinguinal microsurgical technique compared to high ligation and laparoscopic procedure. As Table 2 indicates, the operation time and hospitalization days in the subinguinal group are shorter than those of the other two procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Among the current surgical procedures for treatment of PCS, laparoscopy and transcatheter embolotherapy have been used with good symptomatic relief, but with a tendency for later recurrence of pelvic pain in some cases (4 -9). Since anatomical venous variations are common (10,11), it is important to know the anatomy of these vessels for treatment planning (12,4). The diagnosis of PCS has usually been suggested by venography and ultrasound with Doppler (13)(14)(15)(16)(17)(18)(19), but ultrasound does not depict the gonadal veins.…”
mentioning
confidence: 99%